2011
DOI: 10.1016/j.bbi.2010.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Negative affective responses to a speech task predict changes in interleukin (IL)-6☆

Abstract: Laboratory studies show that individuals differ appreciably in the magnitude of their inflammatory responses to acute psychological stress. These individual differences are poorly understood, yet may contribute to variation in stress-associated disease vulnerability. The present study examined the possibility that affective responses to acute stress contribute to these differences. For this purpose, 102 relatively-healthy community volunteers (mean age 50 years; 60% female; 91.2% white) performed an acute stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 38 publications
9
93
1
3
Order By: Relevance
“…Our patients were homogeneous in age and had not received any previous treatment. This is quite important because it is reported in the literature that sE-cad and/or IL-6 values can be affected by age, treatment or circadian rhythm (25)(26)(27), even if there is no agreement among all authors particularly regarding sE-cad (25,28). Moreover, as described in Patients and methods, blood samples were taken at least three days after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients were homogeneous in age and had not received any previous treatment. This is quite important because it is reported in the literature that sE-cad and/or IL-6 values can be affected by age, treatment or circadian rhythm (25)(26)(27), even if there is no agreement among all authors particularly regarding sE-cad (25,28). Moreover, as described in Patients and methods, blood samples were taken at least three days after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…As not all studies addressing this relationship have reported a positive association between increased inflammation and these anxiety disorders, the importance of factors such as population assessed (community vs clinical), clinician-administered vs self-reported measures of anxiety disorder diagnosis, sociodemographic factors of individuals studied (eg, sex), and co-morbid mental and physical health problems must be considered. Looking more generally at anxiety and associations with proinflammatory markers in non-patient populations, researchers have found evidence that anxiety is related to higher concentrations of CRP and peripheral cytokines (Brennan et al, 2009;O'Donovan et al, 2010;Pitsavos et al, 2006) and predicts increased inflammatory response following acute stress (Carroll et al, 2011;Moons et al, 2010;Moons and Shields, 2015), demonstrating that anxiety and fear even at non-clinical levels impacts the immune response in important ways. There remains a great deal to understand about the association between anxiety disorders and inflammation, and more research is needed before any clear conclusions can be made.…”
Section: Fear-and Anxiety-based Disorders and Inflammationmentioning
confidence: 99%
“…should remain low to avoid emotional and systemic disturbances (MEYER; DA SILVA, 1999;CARROLL et al, 2011;DE ALMEIDA et al, 2013;GOMES DA SILVA et al, 2013). Sheltered dogs present behavior pattern similar to that of owned dogs, although interaction with the environment and other dogs were greater.…”
Section: Task Different Authors Consider Different Cortisol Values Amentioning
confidence: 99%
“…It has been reported that cortisol influences learning in dogs under stress (HAUBENHOFER; KIRCHENGAST, 2007;HAVERBEKE et al, 2008). IL6 participates in the first general inflammatory response to any injury (BLACK, 2002), including psychic and immediate source as acute stress (HEINRICH et al, 2003;NAS et al, 2011;IZAWA et al, 2013a), and can interfere with cognitive performance, since it stimulates aggression when acting in the limbic system and amygdala (ARHANT et al, 2010;CARROLL et al, 2011;DE ALMEIDA et al, 2013). However, we should question if these newly housed animals are not even more stressed during training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation